Shaman poetics (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The elaboration of a shaman poetics aims to put extra-Western and Western aesthetic-political propositions into interaction. Specifically, it wants to remove shamanic practical philosophy from the background of the forest scene and bring it to the forefront of a plurinational Brazilian figuration, generating meanings through interethnic, interartistic, intertextual co-presences. To this end, it outlines experimental notions based on the complex conception of the dream-relational-virtual plane experienced by the shaman, in order to review some authors and modern scenic-performative and literary works; investigating resonances of it in contemporary letters, arts and indigenous voices.
Keywords: shamanism; cosmic politics; mythopoetics; humans and non-humans; virtual beings